The influence of oil supply and cylinder liner temperature on friction, wear and scuffing behavior of piston ring cylinder liner contacts – A new model test. (February 2016) - Obert, Petra; Müller, Torben; Füßer, Hans-Jürgen; Bartel, Dirk
Abstract: A reciprocating model test has been developed, which reproduces real load situation of the contact condition between the piston-ring and cylinder liner at fired top dead center (FTDC) of internal combustion engines. Friction, wear, and load carrying capacity (LCC) were studied as a function of temperature, oil supply rate, and normal force for a honed gray cast iron liner and a chromium plated piston ring. The results show similar liner wear to the ones in actual fired engine tests were obtained as long as normal forces that correspond to engine combustion pressures were applied. Also, a considerable dependency of the LCC on temperature and oil supply rate was found. However, oil supply rate did not influence coefficient of friction (COF) as much as expected. highlights: New test for wear, scuffing, and friction behavior of ring liner contact. Large influence of temperature and oil supply on the load carrying capacity. Determination of scuffing limits. No observable influence of temperature on cylinder liner wear. New method for continuous lubrication of tribological contacts.